Socialization of Clean Wound Care for Post Operative Wounds in Cempaka Room 2 Kartini Karanganyar Regional Hospital - Wahyuni, Endah Sri; Azzahra, Aulia Firly; Cantika O, Azzahra Amanda; Agustin, Cahya Tri; Dewi, Diah; Kharisma, Intan; Barokah, Umi; Purwoko, Bambang (CV. Rayyan Dwi Bharata, 2025)
A wound is a disruption in tissue continuity due to injury or surgery. There are a lot of surgical wounds in Cempaka 2 ward, but there are still many patients and families who don't know how to care for post-operative wounds, so outreach needs to be done. The aim of this outreach is to increase patient and family knowledge in post-operative wound care. The method for implementing this socialization is the lecture and demonstration method. The results of the data obtained were that before the socialization regarding appropriate post-operative wound care was carried out in the Cempaka Room 2, 0 people (0%) were in the good category, 0 people were good (0%), 15 people were less (100%). After conducting socialization about appropriate post-operative wound care in the Cempaka 2 Room with a good category of 15 people (100%), sufficient 0 people (0%), less than 0 people (0%). Based on the community service that has been carried out in Ward Cempaka 2 Kartini Karanganyar Regional Hospital with the theme Socialization of Clean Wound Care in Post Operative Wounds with 15 patients who are very enthusiastic and already know how to carry out post operative wound care correctly as evidenced by the accuracy in answering questions given by speaker.